2013
DOI: 10.1371/journal.pone.0076702
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Pain-Related Stress Predicts Cortical Thickness at Age 7 Years in Children Born Very Preterm

Abstract: BackgroundAltered brain development is evident in children born very preterm (24–32 weeks gestational age), including reduction in gray and white matter volumes, and thinner cortex, from infancy to adolescence compared to term-born peers. However, many questions remain regarding the etiology. Infants born very preterm are exposed to repeated procedural pain-related stress during a period of very rapid brain development. In this vulnerable population, we have previously found that neonatal pain-related stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(170 citation statements)
references
References 81 publications
(91 reference statements)
4
162
1
3
Order By: Relevance
“…Comparing the MRI scans of the children born preterm with those of healthy controls, which were obtained for other follow-up studies of our department [23], we found no differences in either cortical thickness or brain volumes after correction for age, gender, total brain volume, and multiple testing (data not shown). We expected thinning of the cortex, as this was found in a study in 42 children born preterm with a median age of 7.8 years (IQR 7.7-8) [13]. The explanation possibly lies in the fact that the median gestational age in our study group was higher: 31.1 weeks (range 26.1-36.3) versus 29.7 weeks (range 24-32).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Comparing the MRI scans of the children born preterm with those of healthy controls, which were obtained for other follow-up studies of our department [23], we found no differences in either cortical thickness or brain volumes after correction for age, gender, total brain volume, and multiple testing (data not shown). We expected thinning of the cortex, as this was found in a study in 42 children born preterm with a median age of 7.8 years (IQR 7.7-8) [13]. The explanation possibly lies in the fact that the median gestational age in our study group was higher: 31.1 weeks (range 26.1-36.3) versus 29.7 weeks (range 24-32).…”
Section: Discussionmentioning
confidence: 53%
“…A greater number of invasive procedures in children born preterm are associated with abnormalities in white matter brain structure associated with lower intelligence [12]. Pain-related stress is associated with a thinner cortex [13] and with changes in functional cortical activity that are negatively correlated with visual-perceptual functioning during childhood [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Caution is increased for preterm infants because their neurodevelopment may be compromised by inappropriate exposure to either stress or drugs. For example, in preterm infants born < 32 wk gestation, the degree of neonatal pain and stress correlated with cortical thickness at 7 y of age, raising concerns about the long-term negative effects of early pain exposure (28). The increasing use of off-label DEX for neonatal sedation compels examination of the consequences of prolonged early DEX exposure.…”
Section: Dex Effects In Hypothermic Neonatal Ratsmentioning
confidence: 99%
“…For example, when preterm newborns experience pain-related stress, there is significantly thinner cortex in a variety of cerebral regions, but predominately in the frontal and parietal lobes [26]. …”
Section: Preterm Brain Injurymentioning
confidence: 99%